Penyuluhan Stunting sebagai Upaya Peningkatan Pemahaman Masyarakat di Jorong Koto Gadang, Nagari Lubuk Malako - Nurwahidah Wafa Ihsani; Salsabila Maulidia; Tri Agusman Halawa; Rando Rafif Tirandika; Rino (Universitas Negeri Padang, 2026)
Stunting remains a significant public health concern in Indonesia, particularly in rural areas with limited access to health information. This article presents the results of a community service activity in the form of stunting counseling conducted by students of the Kuliah Kerja Nyata (KKN) program of Universitas Negeri Padang at Posyandu Aster I, Jorong Koto Gadang, Nagari Lubuk Malako, Sangir Jujuan District, Solok Selatan Regency, January 20, 2026. The activity aimed to improve community understanding, especially among mothers with toddlers, regarding the causes, impacts, and prevention of stunting. The method used was direct counseling through the delivery of material using visual media, discussions, and question-and-answer sessions in collaboration with local posyandu cadres. The results indicated that the activity was well implemented and received positive responses from the community, as reflected in participants’ enthusiasm and active participation. This activity is expected to enhance community awareness in efforts to prevent stunting from an early stage.